Factors that influence patient preferences for virtual consultations in an orthopaedic rehabilitation setting: a qualitative study. Issue 2 (25th February 2021) - Gilbert, Anthony W; Jones, Jeremy; Stokes, Maria; May, Carl R
Abstract : Objectives: To identify, characterise and explain factors that influence patient preferences, from the perspective of patients and clinicians, for virtual consultations in an orthopaedic rehabilitation setting. Design: Qualitative study using semi-structured interviews and abductive analysis. Setting: A physiotherapy and occupational therapy department situated within a tertiary orthopaedic centre in the UK. Participants: Patients who were receiving orthopaedic rehabilitation for a musculoskeletal problem. Occupational therapists, physiotherapists or therapy technicians involved in the delivery of orthopaedic rehabilitation for patients with a musculoskeletal problem. Results: Twenty-two patients and 22 healthcare professionals were interviewed. The average interview length was 48 minutes. Four major factors were found to influence preference: the situation of care (the ways that patients understand and explain their clinical status, their treatment requirements and the care pathway), the expectations of care (influenced by a patients desire for contact, psychological status, previous care and perceived requirements), the demands on the patient (due to each patients respective social situation and the consequences of choice) and the capacity to allocate resources to care (these include financial, infrastructural, social and healthcare resources). Conclusion: This study has identified key factors that appear to influence patient preference for virtual consultations in orthopaedic rehabilitation. A conceptual model of these factors, derived from empirical data, has been developed highlighting how they combine and compete. A series of questions, based on these factors, have been developed to support identification of preferences in a clinical setting.